Genomic timetree and historical biogeography of Caribbean island ameiva lizards (Pholidoscelis: Teiidae). Issue 17 (1st August 2017) - Tucker, Derek B.; Hedges, Stephen Blair; Colli, Guarino R.; Pyron, Robert Alexander; Sites, Jack W.
Abstract: The phylogenetic relationships and biogeographic history of Caribbean island ameivas ( Pholidoscelis ) are not well‐known because of incomplete sampling, conflicting datasets, and poor support for many clades. Here, we use phylogenomic and mitochondrial DNA datasets to reconstruct a well‐supported phylogeny and assess historical colonization patterns in the group. We obtained sequence data from 316 nuclear loci and one mitochondrial marker for 16 of 19 extant species of the Caribbean endemic genus Pholidoscelis . Phylogenetic analyses were carried out using both concatenation and species tree approaches. To estimate divergence times, we used fossil teiids to calibrate a timetree which was used to elucidate the historical biogeography of these lizards. All phylogenetic analyses recovered four well‐supported species groups (clades) recognized previously and supported novel relationships of those groups, including a ( P. auberi + P. lineolatus ) clade (western + central Caribbean), and a ( P. exsul + P. plei ) clade (eastern Caribbean). Divergence between Pholidoscelis and its sister clade was estimated to have occurred 25 Ma, with subsequent diversification on Caribbean islands occurring over the last 11 Myr. Of the six models compared in the biogeographic analyses, the scenario which considered the distance among islands and allowed dispersal in all directions best fit the data. These reconstructions suggest that the ancestor of this group colonized either Hispaniola or Puerto Rico from Middle America. We provide a well‐supported phylogeny of Pholidoscelis with novel relationships not reported in previous studies that were based on significantly smaller datasets. We propose that Pholidoscelis colonized the eastern Greater Antilles from Middle America based on our biogeographic analysis, phylogeny, and divergence time estimates. The closing of the Central American Seaway and subsequent formation of the modern Atlantic meridional overturning circulation may have promoted dispersal in this group. Abstract : The phylogenetic relationships and biogeographic history of Caribbean island ameivas ( Pholidoscelis ) are not well‐known because of incomplete sampling, conflicting datasets, and poor support for many clades. We obtained sequence data from 316 nuclear loci and one mitochondrial marker for 16 of 19 extant species of the Caribbean endemic genus. We propose that Pholidoscelis colonized the eastern Greater Antilles from Middle America based on our biogeographic analysis, phylogeny, and divergence time estimates.